Minimization of time-averaged and unsteady aerodynamic forces on a thick flat plate using synthetic jets. (April 2015) - Ben Chiekh, Maher; Ferchichi, Mohsen; Béra, Jean-Christophe; Michard, Marc
Abstract: This article reports an experimental investigation on the reduction of the aerodynamic forces on a model consisting of an elongated blunt trailing edge plate using an active control system based on an open-loop, periodic actuation using synthetic jets. Measurements using PIV were conducted at two Reynolds numbers Re h, based on the thickness of the plate h, of about 7200 and 14 400. The control arrangement consisted of two synthetic jet actuators coupled to two slots placed symmetrically along the model base. The synthetic jets were operated either in-phase or anti-phase (180° out-of-phase) with actuation frequencies of 50 Hz and 100 Hz. Both in-phase and anti-phase actuations were found to be effective in vortex shedding suppression and achieved considerable reduction of the time-averaged drag coefficient, C ¯ D . For Re=7200 and actuation frequency of 50 Hz, both in-phase and anti-phase actuations resulted in a negative C ¯ D, suggesting that the synthetic jets acted as a propulsive device. The effectiveness of both control strategies was further evaluated by their capability of reducing the amplitudes of the oscillating drag and lift (normal force) coefficients C ˜ D and C ˜ N respectively. The experimental results showed that the in-phase actuation decreased the amplitude of the oscillating drag coefficient by about 25% compared to that of the natural wake but C ˜ D remained periodic with a frequency of the actuation. More importantly, in-phase actuation was found to result in a considerable decrease (nearly by one order of magnitude) in the amplitude of the oscillating normal force coefficient, C ˜ N . In contrast, the anti-phase actuation increased the amplitudes of both the oscillating lift and drag coefficients by nearly 95% and 30% respectively compared to the natural wake. Highlights: Experiments on minimising the aerodynamic forces on a flat plate using synthetic jets. In-phase actuation suppressed vortex shedding and reduced the time-averaged drag. In-phase actuation reduced the amplitudes of the unsteady lift and drag. Anti-phase actuation suppressed vortex shedding and reduced the time-averaged drag. Anti-phase actuation led to higher amplitudes of the oscillating drag and lift forces.